Digitized Radio broadcast seeker (DRBS) - Sithole, Simbisai Mfunani (Department of Electrical Engineering, 2026)
The use of Software Defined Radio (SDR) has greatly increased the flexibility and programmability of radio systems due to the implementation of radio functions in software. The transfer of traditionally hardware-based signal processing to the software domain enables web SDR receivers to be hosted on the internet as data streaming services. Hosting SDR receivers online allows many users to tune in and listen to broadcast transmissions simultaneously. While significant advancements have been made in SDR hardware technology and making data easily accessible to users, developer productivity has been lacking. The market lacks a simple software development kit that would enable researchers and developers to experiment and create innovative software applications using existing data and components. The aim of this project is to develop an application framework that provides a collection of pre-built modules, components, code libraries, tools and Application Programmable Interfaces (API) that will allow developers to quickly create innovative applications using broadly available Software Defined Radio (SDR) data by leveraging pre- developed infrastructure. The Digitized Radio Broadcast Seeker (DRBS) application as an implementation of the application framework provides a platform for web streaming that aggregates web SDRs and helps developers search for broadcast transmissions of interest as well as build solutions around the streamed transmissions. The research project demonstrated that DRBS could be used to monitor Morse code signals to detect emergencies such as distress calls, weather alerts and other critical broadcasts. After conducting latency and average server response time performance tests, it was concluded that despite the additional infrastructure layer, the DRBS application did not add significant overhead to the signal processing path and could be considered for additional use cases such as identifying FM radio stations and analyzing spectrum usage across different geographical regions.